Control of a stair climbing wheelchair - Nor Maniha Abdul Ghani; M.O. Tokhi; A.N.K Nasir; S. Ahmad (Institute of Advanced Engineering and Science, 2012)
This paper presents investigations into the control of a stair climbing wheelchair particularly for indoor usage. A virtual wheelchair model is developed using Visual Nastran software and linked with Matlab/Simulink for control purposes. The goals are to have a simple, compact and stable stairs climbing wheelchair in order to complete the ascending and descending tasks. The challenges are to ensure the wheelchair seat always stay at the upright position and to control both the front and rear wheel motors while climbing. PID control is used to provide appropriate torque to both front and rear wheels as well as at to the wheelchair seat during climbing. Results show that the wheelchair movement can be controlled smoothly and the seat maintained at the desired position with the adapted approach.DOI: http://dx.doi.org/10.11591/ijra.v1i4.795